Study Of The Use Of Antihypertensive Drugs In Ischemic Stroke Patients In The Inpatient Care Facilities Of “X” Regional Hospital, Semarang City - Sulistiyanto; Anggoro, Barry; R.A, Shelma (LPPM Akademi Farmasi Imam Bonjol Bukittinggi, 2025)
Stroke is a sudden brain injury caused by a lack of blood flow and is the leading cause of disability in adults, Symptoms include facial, speech, memory, and vision problems. There are two types of strokes, ischemic and hemorrhagic, with ischemic stroke being the most common. The prevalence of stroke in Central Java places it among the 11 provinces with the highest stroke prevalence rate in Indonesia. The use of antihypertensive therapy that is not suitable for stroke patients has the potential to worsen the situation. This study aims to find out about the use of antihypertensive drugs in terms of age, gender, service status, drug use patterns, and rationality of drug use. This research is descriptive, collecting data retrospectively. The sampling method used is purposive sampling. The study results showed that there were 57 male patients (54.80%) and 47 female patients (45.20%). The largest age range of the studied sample was the elderly (46-65 years old), which included 59 patients (56.73%). Most of the patients used BPJS services with a total of 101 patients (97.12%). The most common comorbid disease is hypertension hyperlipidemia was recorded as many as 15 cases (14.15%). The most common type of antihypertensive treatment given was monotherapy from the CCB group with a total of 22 cases (20.75%). From the evaluation of the use of drugs in this study, it was found that 100.00% patient accuracy, 50.94% medication accuracy and dosage accuracy of 49.06%.